Hepatitis Delta Virus Testing, Prevalence, and Liver-Related Outcomes Among US Veterans With Chronic Hepatitis B - Robert J. Wong; Zeyuan Yang; Janice H. Jou; Binu V. John; Joseph K. Lim; Ramsey Cheung (Gastro Hep Advances)
Background and Aims: Hepatitis delta virus (HDV) infection in patients with chronic hepatitis B (CHB) is associated with worse liver-related outcomes. We aim to comprehensively evaluate HDV testing, diagnosis, and liver-related outcomes among a national cohort of US Veterans with CHB. Methods: US Veterans with CHB from 2010 to 2023 were evaluated to determine trends in HDV testing (anti-HDV antibody, HDV RNA) and proportion positive among those tested. HDV positive patients were 1:2 propensity score matched to CHB patients who were HDV negative to evaluate incidence (per 100,000 person-years) of cirrhosis, hepatic decompensation, or hepatocellular carcinoma using competing risks Nelson-Aalen methods for estimating cumulative hazards. Results: Among the 27,548 CHB patients identified, 16.1% completed HDV testing, among whom 3.25% (n = 144) were positive. After excluding patients with cirrhosis or HCC at baseline, 71 patients with HDV (median follow-up 5.3 years, interquartile range 2.5–7.6) were propensity score matched to 140 CHB patients without HDV (median follow-up 4.5 years, interquartile range 2.6–8.1). Compared to CHB patients without HDV, those with concurrent HDV had significantly greater incidence of cirrhosis (4.39 vs 1.30 per 100,000 person-years, P < .01) and hepatic decompensation (2.18 vs 0.41 per 100,000 person-years, P = .01). Conclusion: Among a national cohort of US Veterans with CHB, low rates of HDV testing were observed. This is concerning given that patients with concurrent HDV infection had >3 times and >5 times greater risks of cirrhosis and hepatic decompensation, respectively, compared to CHB patients without HDV, highlighting the importance of timely HDV diagnosis and treatment.